Establishing grazing and grazing-excluded patches increases plant and invertebrate diversity in a Mediterranean oak woodland - Bugalho, Miguel N; Lecomte, Xavier; Gonçalves, Merícia; Caldeira, Maria C; Branco, Manuela (Forest Ecology and Management, 2011)
Grazing is a global, dominant land use affecting biodiversity and ecosystem processes. In Mediterranean ecosystems grazing is a major ecological and evolutionary driver but, surprisingly, there is little information on the use of grazing as a tool to manage biodiversity in these ecosystems. We conducted an experiment to assess if establishing grazing and small scale grazing-excluded areas would increase plant and invertebrate diversity in a Mediterranean evergreen oak woodland. Plant community traits were different between treatments. Biomass of herbs (176.7±18.3 gm−2 vs 100.4±10.6 gm−2) and litter (291.0±38.3 gm−2 vs 186.8±26.4 gm−2), as well as the total cover of legumes (0.83±0.05 vs 0.91±0.03) were higher, and the proportion of bare ground (0.83±0.05 vs 0.91±0.03) was lower, in ungrazed plots. There were no differences in the number of plant species between treatments. Some plant species and invertebrate taxa were recorded exclusively in grazed or ungrazed plots. Invertebrate detritivores and sap sucking insects were more abundant in ungrazed plots. Ant assemblages were functionally different between treatments: Honeydew-gatherer ants were associated with ungrazed and higher plant biomass plots, and seed-eaters as well as aggressive predator ant species were associated with grazed, open habitat, plots. Management practices that maintain grazing and small scale grazing-excluded areas can increase habitat heterogeneity and promote herbaceous plant and invertebrate diversity at the local level.
Keywords: Cork oak; Deer; Grazing management; Holm oak; Land-use; montados